Advanced Training of Intellectual Property Documents of Industrial Designs for Goyor Sarong Craftsman in Pemalang District - Waspiah, Waspiah; Rodiyah, Rodiyah; Latifiani, Dian; Setiaji, Dede Alvin (Faculty of Law, Universitas Negeri Semarang, 2020)
Intellectual property is used to increase economic value while providing legal protection for innovative inventions. Goyor Glove, typical of Pemalang, in fact, does not yet have legal protection on Intellectual Property, especially Industrial Design, so that the protection is low and many industrial designs of Goyor sarong are used by others without permission. The methods used to solve the problems in this service program are: (1) Training (workshop), which aims to provide knowledge and skills in quality improvement and product development (2) Product development and application management of the Goyor motif motif to be a description of IP Industrial Design; (3) Assisting and facilitating IP registration of Industrial Designs to be able to increase the economic value of the product; and (4) Monitoring and Evaluation for follow-up plans. Partners in this program, namely the Goyor Sarong Craftsmen in Pemalang District, were given the opportunity to play an active role, from the time of training to mentoring, facilitation and monitoring and evaluation especially during registration and acceleration of obtaining IP Industrial Design certificates craftsmen are given the opportunity to actively provide ideas, criticism in product development and application of management to obtain IP protection. Thus this activity is centered on partners based on the basic needs of partners to develop by increasing the economic value and welfare of the Goyor Gloves craftsman in particular.